Menumbuhkembangkan Budaya Literasi Anak pada Panti Asuhan Universal Anak Indonesia Kota Medan Melalui Pendampingan dengan Menggunakan Metode Group Work - Sitanggang, Vani; Putri , Malida; Ritonga, Fajar Utama (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2023)
The decline in the reading culture has become the main cause, and even the learning culture in schools is gradually disappearing. Although the percentage of school children has increased with the government's compulsory education program, this does not automatically improve the quality of education. Even though children go to school every day, they never really learn, especially due to the low reading culture. School seems to have become a daily routine. Schools play a crucial role in instilling a culture of reading and writing (literacy) in students. Therefore, every school must fully support the cultivation of a reading and writing (literacy) culture. Literacy culture itself is related to fostering reading and writing interest in elementary school children. In fostering an interest in reading and writing, literacy culture is the key to realizing that interest. Consequently, fostering an interest in reading and writing requires several roles, such as facilities and infrastructure in schools, the community, and parents. If these roles are inadequate, it will have a detrimental impact on the sustainability of a good literacy culture.